WTO and regional trade negotiation outcomes : quantitative assessments of potential implications on Bangladesh - Raihan, Selim; Razzaq, Abdur (Dhaka : Pathak Shamabesh, 2007)
On foreign commercial policy of Bangladesh in light of WTO and international trade practices.
Includes bibliographical references and index.
Keywords: Bangladesh -- Commercial policy; World Trade Organization -- Bangladesh; Bangladesh -- Foreign economic relations